Analysis Determinants of Economic Growth in Asian Countries: an Empirical Study of Middle-Income and High-Income Countries - Saniyyah, Reidah Daffa; Istiandari, Debby Nindya (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
Every country in the world always expects increased economic growth. So in analyzing the factors that affect economic growth, there are many determinants. However, the IMF reports that the economy in Asia is slowing down due to declining trade. This study uses secondary data with panel data regression method analysis. The results showed that in both middle-income and high-income Asian countries, economic freedom has a positive and insignificant effect on economic growth. While trade openness has a negative and significant effect. For FDI variables and LFPR have a positive and significant effect. While the country dummy variable shows economic growth in middle income and high income in Asian countries shows the results that there are significant differences.